Changing Livelihoods, Development, and Cultural Practices: Reshaping Forests Among the Tau Taa Vana People - Humaedi, Muhammad Alie; Nadzir, Ibnu; Himmi, Setiawan Khoirul; Astutik, Sri; Tessa, Adhis; Andari, Rosita Novi (Forest and Society, 2024)
The Tau Taa Vana people live in the Bulang Highlands, Tojo Una-Una, in Central Sulawesi Province. The region's development has shaped the marginalization of forest-dwelling and forest-adjacent communities. From the 1980s to the 1990s, illegal logging networks served as the power holders, backed by Indonesia’s authoritarian regime of that time. Illegal logging destroyed a large part of the Tau Taa Vana's sacred forest (pengale kapali). As part of the massive logging agenda, the government launched many legal programs that further isolated the Tau Taa Vana people from their land. The first program was transmigration in 1995-1998, which converted sacred forests into plantation areas and worker camps. Meanwhile, the Tau Taa Vana people were forced to relocate from their forest livelihoods (pengale lipu). In 2014, development shifted towards government-supported gold and nickel extraction identified in the Tau Taa Vana people's traditional regions. The government's planned material extraction of the region has forced the Tau Taa Vana people to adapt traditional environmental management systems. In the past, the forest had three main functions, as the source of food, medicine, and livelihoods. Nowadays, those functions are reduced drastically and the sacred forest with the Kaju Marangka'a region as the center has lost its cultural importance. Tau Taa Vana people today use the remaining forests as the center of their resistance movements and consider it as their last bastion for cultural preservation. In this regard, the role of traditional healers (tau valia) has become even more critical amidst the lack of traditional elders.